2017
DOI: 10.1177/0022219417708169
|View full text |Cite
|
Sign up to set email alerts
|

Early Writing Intervention: A Best Evidence Synthesis

Abstract: The purpose of this best evidence synthesis was to identify promising interventions that align with a theoretical model of early writing development, targeting three components of early writing: transcription, text generation, and self-regulation. We determined the extent to which these interventions are effective for children who struggle with early writing skills, by calculating effect sizes for group and single-subject designs, and we examined the overall quality of the research. Twenty-five studies met inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Limited evidence exists in general on the efficacy of instructional programs that target text generation directly and primarily (McMaster, Kunkel, Shin, Jung, & Lembke, 2018). In a best-evidence review, McMaster et al (2018) showed that 17 out of 25 studies addressing Grades 1 to 3 targeted text generation in multicomponent interventions; however, most of them did not examine the specific contribution of training text generation processes.…”
Section: The Efficacy Of Text Generation Interventions and Interventimentioning
confidence: 99%
See 2 more Smart Citations
“…Limited evidence exists in general on the efficacy of instructional programs that target text generation directly and primarily (McMaster, Kunkel, Shin, Jung, & Lembke, 2018). In a best-evidence review, McMaster et al (2018) showed that 17 out of 25 studies addressing Grades 1 to 3 targeted text generation in multicomponent interventions; however, most of them did not examine the specific contribution of training text generation processes.…”
Section: The Efficacy Of Text Generation Interventions and Interventimentioning
confidence: 99%
“…Limited evidence exists in general on the efficacy of instructional programs that target text generation directly and primarily (McMaster, Kunkel, Shin, Jung, & Lembke, 2018). In a best-evidence review, McMaster et al (2018) showed that 17 out of 25 studies addressing Grades 1 to 3 targeted text generation in multicomponent interventions; however, most of them did not examine the specific contribution of training text generation processes. Other meta-analyses that examined the effectiveness of writing interventions with elementary school children (Graham, McKeown, Kiuhara, & Harris, 2012;Graham & Perin, 2007) or older writers (Graham & Perin, 2007) analyzed four types of instructional programs focused primarily on text generation-explicit teaching of grammar, sentence combining, teaching text structure, and emulating good texts-and reported only small to moderate efficacy (effect sizes from 0.25 to 0.59) for those programs.…”
Section: The Efficacy Of Text Generation Interventions and Interventimentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these papers (Coker et al, 2017; Costa et al, 2017) offer productive approaches and yet highlight the complexity of identifying struggling writers early in their schooling. McMaster, Kunkel, Shin, Jung, and Lembke (2017) conducted a rigorous best evidence synthesis on interventions for struggling writers in the primary grades. Their results offer useful insights for teachers and researchers interested in effective approaches for whole class and small group instruction with struggling writers.…”
Section: Articles In This Issuementioning
confidence: 99%
“…Transcription skills have been shown to play a critical role in early writing development (Graham & Harris, 2000), because proficient transcription skills free up cognitive resources needed for higher-level writing skills (such as generating ideas, selecting appropriate words, constructing strong sentences, and so on). The Simple View of Writing has been supported by empirical studies examining the effects of transcription interventions to improve text generation skills (see McMaster, Kunkel, Shin, Jung, & Lembke, 2017).…”
mentioning
confidence: 99%